Effect of impurities on mechanical relaxation in niobium - Florêncio, Odila; Silva Jr, Paulo Sergio; Botta Filho, Walter José; Grandini, Carlos Roberto [UNESP] (ABM, ABC, ABPol, 2003)
Measurements of internal friction as a function of temperature were performed in samples of Nb containing different amounts of substitutional (Zr) and interstitial (O, N) solutes. These data were resolved using the method of successive subtraction, into a series of constituent Debye peaks corresponding to different interactions. For each relaxation process we obtained the height (Q-1max) and temperature (Tp) of the peak, the activation energy (E) and the relaxation time (t0). The height, shape and temperature of the peaks depend on the concentration of interstitial and substitutional elements. With the addition of substitutional solute one can observed interactions between the two types of solutes (substitutional and interstitial), showing that the random distribution of the interstitial atoms was affected by presence of substitutional atoms. The peaks observed were associated with matrix-interstitial (Nb-O, Nb-N) and substitutional-interstitial (Zr-O) interaction processes.
Keywords: niobium; niobium alloys; interstitial elements; internal friction